A numerical study on the correlation of ductile crack extension in Ni-based clad pipe girth welds with circumferential surface cracks and clamped SE(T) specimens. (January 2023) - Afzalimir, Seyed H.; Ruggieri, Claudio
Abstract: This work describes a numerical investigation on the relationships between ductile crack extension in Ni-based clad pipe girth welds and an API X80 pipeline steel with circumferential surface cracks and SE(T) specimens under fixed grip conditions. A primary objective is to gain further insight and understanding of the effects of constraint on ductile tearing behavior in piping components with dissimilar girth welds and how well crack growth resistance curves measured using single edge notched tension fracture specimens correlate with ductile fracture behavior in circumferentially surface cracked pipes. The numerical description of CTOD − R curves employs a computational cell approach incorporating the Gurson–Tvergaard (GT) constitutive model to simulate ductile crack extension in the crack configurations analyzed. The numerical analyses consider predictions of ductile crack growth in 3-D models of circumferentially cracked pipes with varying crack depth over pipe thickness ratio, a / t, from measured J -resistance curves derived from fracture resistance testing of clamped SE(T) specimens. The analyses also focus on comparing predictions of ductile crack extension using two different definitions for the CTOD. Highlights: Extensive crack growth analyses on SE(T) specimens with dissimilar CRA welds. Extensive ductile tearing analyses on circumferentially cracked pipes with dissimilar CRA welds. CTOD fracture resistance curves determined on the basis of two CTOD definitions. Relatively weak effect of CTOD definition on CTOD − R curves. Clamped SE(T) specimens correlate well with circumferentially cracked pipes. Homogenization procedure simplifies the modeling of a V-groove dissimilar girth weld.